The experience of representation of the applied terminological system by means of terminological network - Asadova Alina Yu. (Актуальные проблемы филологии и педагогической лингвистики, 2020)
The article is devoted to the study of the English-language Digital Photography terminological units by building a terminological network, namely, identifying key categories of special notions and system relations between the corresponding terminological units to prove that the analyzed terminological system is mainly applied. These features of the terminological system are identified and classified by building a terminological network. The primary task was to determine the main categories of special notions that are frequently verbalized by the English-language Digital Photography terminological units drawing on the example of the analysis of definitions of key terms, as well as to calculate the types of relations between the designated categories. In this regard, the study of a term as a system unit that occupies a clearly defined place in the subsystem of professional lexis becomes possible with the help of a terminological semantic network, which shows that the relationships and categories which the correlating terms belong to are not random. Digital Photography terminological units in the modern English language, which have been taken from the English-language online dictionaries, reference books, glossaries, and Internet portals dedicated to the topic in question, have served as the material for the research. Terms of one category can be associated with the representatives of other categories by means of recurrent system relationships, thus forming prototypical schemes of interaction between terminological units. During the work the two groups of terms have been allocated: the first one consists of “material” terminological units, verbalizing natural objects/phenomena, natural / artificial substances, loci (places, locations), instruments and tools (parts of tools), simple and complex mechanisms and their components, natural / artificial materials, artificially created loci (places) or constructions. The second group includes non-material terms that nominate the category “actor”, processes, situations, characteristics, ideal phenomena. The predominant categories of notions in the sphere of Digital Photography are components of mechanisms / tools, processes, ideal phenomena, complex mechanisms, characteristics / parameters, which indicates the fact that the Digital Photography terminological system is mainly applied. The study has revealed that the most frequent types of system relations between notions and their verbalizers-the corresponding English-language Digital Photography terms are: AKO (system relations between hyperonym and hyponym), ISA (system relations of coincidence or inclusion in a set), SR (system relations between referents which make up the subject of influence and the result obtained within the same process), which also indicate the predominantly applied nature of the Digital Photography terminological system.